2021
DOI: 10.2991/aer.k.211222.028
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review of Potential Development of Photovoltaic (PV) Systems at Electric Vehicle Charging Stations to Support Clean Energy in Indonesia

Abstract: Energy needs are always increasing in various sectors of life. Indonesia, which is below the equator, has extraordinary advantages, one of which is its high potential for solar energy. With high sun exposure throughout the year, Indonesia has the potential to use it to generate electrical energy. One of the biggest energy needs is transportation needs. To be in line with the energy mix agenda with energy sustainability, it is necessary to implement the use of clean energy in the transportation sector. Indonesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…The results showed that the variable of social and environmental considerations had a direct effect on the balance of business sustainability. This is in accordance with research (Maghfuri et al, 2022) which states that social factors, such as the state of society and environmental factors, such as reducing gas emissions will have a positive impact on companies and industries in order to create product production that is beneficial to society and does not damage the surrounding environment. The results of the study state that the renewable energy transition variable has an indirect effect on the balance of business sustainability through social and environmental considerations as intervening variables.…”
Section: Discussionsupporting
confidence: 88%
“…The results showed that the variable of social and environmental considerations had a direct effect on the balance of business sustainability. This is in accordance with research (Maghfuri et al, 2022) which states that social factors, such as the state of society and environmental factors, such as reducing gas emissions will have a positive impact on companies and industries in order to create product production that is beneficial to society and does not damage the surrounding environment. The results of the study state that the renewable energy transition variable has an indirect effect on the balance of business sustainability through social and environmental considerations as intervening variables.…”
Section: Discussionsupporting
confidence: 88%
“…The MCS using technology Lithium-iron phosphate (LiFeO4) and electric double-layer capacitor (EDLC) as ultracapacitor Kesiapan teknologi MCS menggunakan baterai Lithium-iron phosphate (liFeO4) dan electric double-later capacitor (EDLC) sebagai ultracapacitor can provide adequate facilities for ultrafast charging of batteries (Dwi Atmaja, n.d.). Studies combining the implementation of grid networks and photovoltaic (PV) renewable energy sources have also been carried out, which are supported by information and communication technologies using cloud architecture (Maghfuri et al, 2021) . Due to its flexibility and simplicity, MCS can be used as an alternative to accelerate the availability of electric charging infrastructure.…”
Section: Charging Devices and Connectorsmentioning
confidence: 99%
“…This has prompted various calls to reduce and limit the use of fossil energy and replace it with renewable New Energy (EBT). Utilization of EBT or known as clean energy has become a joint action program from various countries in the world, including Indonesia (Anggraini & Indah, 2021;Maghfuri et al, 2021).…”
Section: Introductionmentioning
confidence: 99%